Is Attitudinal Acceptance of Violence a Risk Factor? An Analysis of Domestic Violence Against Women in Pakistan. Issue 7 (April 2021) - Amir-ud-Din, Rafi; Fatima, Shameem; Aziz, Shazia
Violence against women (VAW) is a grave problem in Pakistan, and women from all socioeconomic groups are vulnerable to domestic violence in varying degrees. It is argued that patriarchal definition of gender roles may reinforce the internalized inferiority of women. So, it may not be a mere coincidence that a large number of women in Pakistan justify VAW for various reasons. The objectives of this article are threefold: (a) to identify the drivers of VAW, (b) to see if women's attitudinal acceptance of violence is causally linked with observed violence against women, and (c) to see if attitudinal acceptance of violence mediates between the socioeconomic status of women and observed violence. We used data from the Pakistan Demographic and Health Survey (PDHS) 2012-13. The sample consisted of 3, 265 ever married women aged between 15 and 49 years who were interviewed for domestic violence. We used multivariate logit regression analysis to identify the drivers of VAW and used the Karlson-Holm-Breen (KHB) method for mediation analysis. We found that women's attitudinal acceptance of violence, their childhood experience of violence in their parental household, the education of both husband and wife, and some occupation types significantly predicted their experience of spousal violence. In addition, we found that women's attitudinal acceptance of violence mediated the relationships between socioeconomic factors (education and wealth status) and VAW. The significance of the study lies in the fact that it highlights the need to modify the perceptions of violence through change in educational policy. Among multiple other factors, an increase in the economic status of women is an effective hedge against the risk of spousal violence.